2021
DOI: 10.1038/s41598-021-90754-x
|View full text |Cite
|
Sign up to set email alerts
|

The curcumin analog (PAC) suppressed cell survival and induced apoptosis and autophagy in oral cancer cells

Abstract: PAC (3,5-Bis (4-hydroxy-3-methoxybenzylidene)-N-methyl-4-piperidone), a novel bioactive curcumin analog, has been reported to have anticancer properties against various tumors. However, the anti-cancer effects of PAC on oral cavity squamous cell carcinoma were not studied yet. Our aim is to investigate the anti-oral cancer properties of PAC in vitro, and determine the molecular mechanisms underlying these effects. Viability assays including MTT and LDH were conducted to measure cell proliferation. Flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 49 publications
2
47
0
Order By: Relevance
“…70 Interestingly, several analogs of curcumin are identified their antitumour activity through induction of apoptosis in OSCC. 71,72 In HSC-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 Interestingly, several analogs of curcumin are identified their antitumour activity through induction of apoptosis in OSCC. 71,72 In HSC-…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, curcumin promoted apoptosis by inducing cleaved caspase 3 and cleaved PARP in YD10B OSCC cells at the dose of 10 µM 70 . Interestingly, several analogs of curcumin are identified their antitumour activity through induction of apoptosis in OSCC 71,72 . In HSC‐4 and HSC‐2 human oral cancer cells lines, Dibenzylideneacetone inhibits cell viability by triggering apoptosis at the dose of 5–10 µM 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of magnolol-induced ERK1/2 activation in oral cancer requires further study. Moreover, several studies have revealed that JNK1/2 plays an anti-tumor role in oral cancer and emphasizes its positive role in apoptosis [34][35][36]. Numerous studies have also reported that magnolol inhibits cancer progression [14] or induces apoptosis [13,37] by regulating multiple cellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The human oral cancer cell line Ca9–22 cells were cultured at 37 °C and 5% CO 2 in RPMI-1640 medium (Thermo Fisher Scientific, Burlington, ON, Canada), supplemented with L-glutamine, 5% fetal bovine serum (FBS, Gibco) provided by the same company, and 1% penicillin/streptomycin solution (Sigma-Aldrich, Oakville, ON, Canada). Cell proliferation was bi-evaluated using two MTT and LDH tests as described by Semlali et al 2021 [ 35 , 36 ] and Contant et al 2021 [ 37 ]. For the MTT assay, 10 5 Ca9-22 cells per well containing the sample were seeded in 24-well plates for 24 h. After adhesion and growth of the cells, the culture medium is replaced by a new one containing a solution of MTT at 5 mg∙ml −1 in PBS and left for 3 h at 37 °C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…LDH assay was realized by the LDH Cytotoxicity Detection Kit from Roche, which allows to directly quantify the cell death in culture based on the measurement of lactate dehydrogenase released into growth media. As described in our previous work [ 35 , 36 ], 10 5 cells per well were seeded in 24-well plates containing NPX/pHEMA and NPX/pHPMA with different compositions. After adhesion for 24 h, 50 μL of each supernatant was transferred in triplicate into a 96-well plate and supplemented with 50 μL reconstituted substrate mixture.…”
Section: Methodsmentioning
confidence: 99%